Tiempo y temperatura de tostado sobre el grado de alergia alimentaria en la semilla de zapallo (Cucúrbita Máxima D.) - Mendieta Domínguez, Josselin Iveth (2021)
The proposed research was carried out in the Bromatology laboratory of the ESPAM “MFL”, located at the “El Limón” site, Bolívar canton, province of Manabí. Its purpose is to determine the suitable time and temperature to minimize the food allergenic potential of the pumpkin seed. For its effect, allergenic hemagglutination was determined based on the reference method of the company Castor Ecuatoriana S.A.; whose results were interpreted in food allergy percentages. The combination of the levels of the factors under study generated 6 treatments, which were repeated 3 times; Each unit of study was 20 roasted pumpkin seeds (Cucúrbita Máxima D), performing 3 repetitions of each, giving a total of 18 experimental units. As a result, it was obtained that the treatments with the lowest levels of allergy were T3 (160 ° C x 15min), T5 (140 ° C x 20min) and T6 (160 ° C x 20 min). The KRUSKAL WALLIS statistical test showed that Factor A (roasting time) does not influence the degree of allergy because its p-value > 0,05; while Factor B (roasting temperature), if it significantly influences the degree of allergy. Statistical graphs showed that the best roasting temperature to reduce the degree of food allergy in the pumpkin seed is 160 ° C, which corresponds to the b3, which indicates that the higher the temperature, the lower the degree of allergy and toxicity.